1986
DOI: 10.3171/jns.1986.64.2.0216
|View full text |Cite
|
Sign up to set email alerts
|

Sudden deterioration and death in patients with benign tumors of the third ventricle area

Abstract: Although sudden deterioration and death is a widely recognized complication in patients with benign tumors of the third ventricle area, the exact incidence of this dreaded occurrence is unknown and the reports in the literature on the subject are largely anecdotal. Neither risk factors nor the etiology of the sudden death have been analyzed. The vast majority of these benign tumors are colloid cysts, and the presence and degree of ventricular dilatation and herniation associated with these tumors as cited in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
65
0
1

Year Published

1988
1988
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(68 citation statements)
references
References 14 publications
2
65
0
1
Order By: Relevance
“…Estimates of the risk of rapid clinical deterioration due to acute hydrocephalus in patients with colloid cysts vary widely, from 3% to 35%, with an associated 5%-38% risk of death. 2,4,12,13,17 Historically, these patients were often described as having experienced "sudden deterioration and death," but several more recent studies using modern neuroimaging techniques have demonstrated that nearly all patients with acute obstructive hydrocephalus have progressive symptoms preceding precipitous clinical deterioration. Potential exceptions are the rare instances of acute intralesional hemorrhage or "cyst apoplexy."…”
mentioning
confidence: 99%
“…Estimates of the risk of rapid clinical deterioration due to acute hydrocephalus in patients with colloid cysts vary widely, from 3% to 35%, with an associated 5%-38% risk of death. 2,4,12,13,17 Historically, these patients were often described as having experienced "sudden deterioration and death," but several more recent studies using modern neuroimaging techniques have demonstrated that nearly all patients with acute obstructive hydrocephalus have progressive symptoms preceding precipitous clinical deterioration. Potential exceptions are the rare instances of acute intralesional hemorrhage or "cyst apoplexy."…”
mentioning
confidence: 99%
“…3,16) However, the number of patients with diagnoses of colloid cysts is likely to decrease with age. 6) With aging, colloid cyst cells secrete an amorphous, proteinaceous material resulting in cyst formation and expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic surgery for asymptomatic colloid cysts of the third ventricle remains controversial. 3,15,16) However, the possibility of spontaneous rupture of these cysts should also be kept in mind. If surgery is indicated, the surgical team must ensure that the cyst contents do not spill into the ventricular system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sudden death has been linked to the proximity of cardiovascular centers to the third ventricle or to sudden-onset hydrocephaly 16 . The mechanism of drop attacks has been linked to transient CSF flow blockage; however, as Kelly also stressed, other symptoms are not specific for colloid cysts located in the third ventricle 15,16,17 . Total excision of colloid cysts is recommended in symptomatic cases since simple cyst aspiration is not sufficient 11 .…”
Section: Discussionmentioning
confidence: 99%